ANALISIS DAYA SAING KOMODITI UNGGULAN SEKTOR PERKEBUNAN DI SULAWESI UTARA - Mandei, Juliana R.; Benu, Olfie L.S.; Laoh, O. Esry H.; Oping, Joy M. (EUGENIA, 2008)
ABSTRACT Mandei, J.R. et. al. 2008. Competitiveness Analysis Of Plantation Strategic Sector At North Sulawesi). Eugenia 14 (3) : 361-374. The economic changing of Indonesia, especially at North Sulawesi was fast and not stable in some year latest involve some change. Rupiah fluctuation concerning US dollar and increasing price of goods, include price of production factor influence production cost, become the reason to doing a research about competitiveness of plantation commodity in North Sulawesi. The objectives of the research is to know the competitiveness of plantation commodity in North Sulawesi. The analiysis was of four commodities, that is Coconut, Vanilla, Nutmeg and Clove. Those commodities are the straregic commodities in North Sulawesi. The method used in this analysis is Domestic Resource Cost (DRC) and Effective Rate of Protection (ERP). The research was done from Juli to Agustus. The data used in the research consisted of primary and secondary data. Secondary data were obtained from local government institutions, while primary data were collected from the direct interviews with the farmers on the site. The research indicated that the farm system of Coconut, Vanilla, Nutmeg and Clove cultivated in North Sulawesi Area brought advantages both in private and social aspect. The result showed that profit value was bigger than zero, meaning that the production those commodities in this area were feasible to be increased, given the land was available and there were no alternative commodities that were more profitable. The plantation commodities in North Sulawesi had competitive and comparative advantage. The implication of ths fact showed that those commodities were feasible to be produced due to the efficiency in using the domestic resources and those commodities were feasible to export. Coefisien Domestic Resource Cost (DRC) for Coconut commodity (0.321), Vanilla (0.343), Nutmeg (0.195), and Clove (0.701) was below one and smaller than shadow price, indacated that those commodities were efficient in using domestic resource and had comparative advantage. Effective Rate of Protection (ERP) for Coconut commodity (-0.679), Vanilla (-0.657), Nutmeg (-0.805) and Clove (-0.229) was negative, indicated that those commodity were not needed effective protection and those commodity were privately profitable. Â  Keywords : Â vanilla, coconut